2020
DOI: 10.1016/j.ejrad.2020.109285
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and psychological impact of the COVID-19 outbreak on private practice and public hospital radiologists

Abstract: The COVID-19 pandemic has led to an urgent reorganisation of the healthcare system to prevent hospitals from overflowing and the virus from spreading. Our objective was to evaluate the socioeconomic and psychological impact of the COVID-19 outbreak on radiologists. Material and methods: French radiologists were invited to answer an online survey during the pandemic through mailing lists. The questionnaire was accessible for nine days. It covered socio-demographic information, exposure to COVID-19 at work and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 18 publications
(24 reference statements)
2
35
3
Order By: Relevance
“…We aimed to identify risk factors for anxiety, depression and PTSD in relation to the SARS-CoV-2 epidemic. We did not find some of the risk factors previously reported in the literature, such as female sex, young age, being a nurse or a “frontline worker” or belonging to non-medical staff [1] , [2] , [3] , [6] , [16] , [19] , [20] , [23] , [24] , [25] , [26] , [27] , [28] . This finding might be explained, with regards to age and sex, by the proportion of males and people younger than 25 years in our population.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We aimed to identify risk factors for anxiety, depression and PTSD in relation to the SARS-CoV-2 epidemic. We did not find some of the risk factors previously reported in the literature, such as female sex, young age, being a nurse or a “frontline worker” or belonging to non-medical staff [1] , [2] , [3] , [6] , [16] , [19] , [20] , [23] , [24] , [25] , [26] , [27] , [28] . This finding might be explained, with regards to age and sex, by the proportion of males and people younger than 25 years in our population.…”
Section: Discussioncontrasting
confidence: 86%
“…These percentages are much lower than the 45 to 55% anxiety and 25 to 60% depression observed in previous international reports involving the HAD scale, which were performed at the peak of the epidemic in China and Brazil [16] , [17] , [18] ; it bears mentioning that these reports were based on a lower HAD scale cut-off value (8 points) and included “suspected” anxiety or depressive disorders. When compared to the 2 French studies using the same HAD scale cut-off value as ours (11 points), which disclosed 14.6% and 19% anxiety, and 12% and 9% depression among radiologists and ICU healthcare workers respectively [5] , [6] , the psychological impact in our population is slightly higher than expected. Other French studies used a lower HAD scale cut-off value (8 points) [3] , [7] , but did not mention their cut-off [4] or apply other evaluation scales [9] , which precluded comparisons with our results.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast to the findings reported by Florin et al, 4 we did not observe any statistically significant ( p < 0.05) interaction effects when we stratified for private versus non-private institutions. However, when we stratified for academic versus non-academic institutions, the interaction terms for the following items were found to be statistically significant: gender ( p = 0.03), increased use of personal protective equipment (PPE) as an anticipated effect on clinical practice in one year ( p = 0.04), adequate supply of PPE for patients ( p = 0.03), and teleradiology as a respondent's main setting of practice ( p = 0.04).…”
contrasting
confidence: 99%
“…However, the study has some limitations. First, the psychological impact of COVID-19 is not just about anxiety, symptoms indicative of depression can also be found, as Florin et al demonstrated in a similar study in France, 2 and must be addressed too. Moreover, it wasn't specified if medical history of previous psychiatric disorders was taken into account in the survey.…”
mentioning
confidence: 99%
“…We recognize the study has a large sample, which assures a statistical power, but we propose a more detailed subgroup analysis. For example, a descriptive and differentiating analysis between public and private hospital radiologists would have been useful, since, as exposed in the study of Florin et al, 2 belonging to the workforce of a public hospital may confer a protective effect. In addition, it would have been interesting for part of the sample to be categorized into sites with high and low numbers of COVID-19 patients in order to evaluate if there is a relationship between this exposure and variables such as level of anxiety, workload, financial impact, among others.…”
mentioning
confidence: 99%